2019
DOI: 10.1002/ejic.201801173
|View full text |Cite
|
Sign up to set email alerts
|

Pyrophosphate Prompted Aggregation‐Induced Emission: Chemosensor Studies, Cell Imaging, Cytotoxicity, and Hydrolysis of the Phosphoester Bond with Alkaline Phosphatase

Abstract: Two benzimidazole-based zinc complexes [(Zn) 2 (L2) 2 Cl 2 (DMSO) 2 ] (R1) and [Zn(L2) 2 (NO 3 ) 2 (H 2 O) 2 ] (R2) were synthesized and characterized with various spectroscopic data. The single X-ray structure determination reveals that complex R1 is dinuclear and tetrahedral in geometry, while complex R2 is mononuclear and octahedral in geometry. Further, both zinc complexes were investigated for pyrophosphate sensing in an aqueous medium. Complex R1 is found to be selective towards pyrophosphate; it leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…In the Cambridge Structural Database, there are no deposited structures of the coordination compounds with ligands L1–L4 [ 58 ]. The most similar structurally characterized dinuclear zinc compound is tetrachlorobis{µ-[2-(pyridin-4-yl)-1H-benzimidazole]}dizinc (II), which was obtained in the solvent-free form [ 59 ] and as dimethyl sulfoxide solvate [ 60 ]. The pyridinyl-benzimidazole molecules form bridges via nitrogen atoms of pyridine and imidazole rings.…”
Section: Resultsmentioning
confidence: 99%
“…In the Cambridge Structural Database, there are no deposited structures of the coordination compounds with ligands L1–L4 [ 58 ]. The most similar structurally characterized dinuclear zinc compound is tetrachlorobis{µ-[2-(pyridin-4-yl)-1H-benzimidazole]}dizinc (II), which was obtained in the solvent-free form [ 59 ] and as dimethyl sulfoxide solvate [ 60 ]. The pyridinyl-benzimidazole molecules form bridges via nitrogen atoms of pyridine and imidazole rings.…”
Section: Resultsmentioning
confidence: 99%
“…A more recent study synthesised a benzimidazole‐based zinc complex, which was selective for PP i that enhances its fluorescence. Then, AP activity toward PP i could be monitored via a decrease in fluorescence [54] . Another study reported a sensing strategy with fluorescent carbon quantum dots (CQDs).…”
Section: Detection Methodsmentioning
confidence: 99%
“…Then, AP activity toward PP i could be monitored via a decrease in fluorescence. [54] Another study reported a sensing strategy with fluorescent carbon quantum dots (CQDs). Although this assay was employed to quantify AP, it could potentially be applied to characterise enzyme-substrate kinetics.…”
Section: Detecting Substrates and Non-phosphate Products By Specific ...mentioning
confidence: 99%
“…However, this single signal was greatly perturbed, being replaced by two new broad signals at δ -3.32 and -4.57 upon addition of one equivalent of DFB-Zn 2+ (5 mM). The significant downfield chemical shift values (∆δ = -2.88 and -1.63 ppm) for the P-atoms (Pa and Pb) suggest that they are magnetically unequal [79], and the electron density around each P atom was reduced upon interaction with DFB-Zn 2+ . Based on these results, we postulate that the comparatively higher downfield shifted signal at -3.32 ppm concerns Pa, which contributes with two oxygens for coordination, as shown in Fig.…”
Section: Anion Sensing Studiesmentioning
confidence: 99%